ChemInform Abstract: 3‐Methyl‐4‐oxa‐5‐azahomoadamantane: Alkoxyamine‐Type Organocatalyst for Alcohol Oxidation. Issue 17 (28th April 2014) - Sasano, Yusuke; Murakami, Keiichi; Nishiyama, Tomohiro; Kwon, Eunsang; Iwabuchi, Yoshiharu
Abstract The title organocatalyst exhibits unexpected high catalytic activity in the presence of NaOCl and KBr to oxidize primary and secondary alcohols to their corresponding carbonyl compounds.